The component composition of the total flavonoid fractions from some Ericaceae family and their effect on the NO-stimulating activity of peritoneal macrophages - Ya. E. Reshetov; A. A. Ligacheva; E. S. Trofimova; N. S. Selivanova; S. V. Krivoshchekov; E. V. Basova; E. Yu. Sherstoboev; E. Yu. Avdeeva; I. P. Kaminsky; M. G. Danilets; M. V. Belousov (Разработка и регистрация лекарственных средств)
Introduction. Representatives of the Ericaceae family are quite common in Russia and are promising for the creation of new medicines of plant origin. At the same time, only 4 of them are official. The study of biologically active substances and pharmacological activity of Andromeda polifolia L., Chamaеdaphne calyculata (L.) Moench, Ledum palustre L., Empetrum nigrum L. with rich resource reserves is promising.Aim. Comparative study of the composition of total flavonoid fractions from A. polifolia, C. calyculata, L. palustre, E. nigrum and study of their effect on the NO-stimulating activity of peritoneal macrophagesMaterials and methods. The crushed aboveground part (leafy shoots) was previously depigmented with chloroform, treated with 70 % aqueous acetone, then acetone was removed. Flavonoids were extracted with ethyl acetate from the aqueous phase. The identification of flavonoids was carried out by HPLC (UltiMate 3000 chromatograph) according to the coincidence of retention times and spectral characteristics, the calculation of the content was carried out by simple normalization. The effect of the samples on nitric oxide production was studied on macrophages of C57BL/6 mice. Endotoxin control in the samples was carried out using a LAL test and cell incubation in the presence of polymyxin B.Results and discussion. The composition of flavonoid fractions from A. polifolia, C. calyculata, L. palustre and E. nigrum has been studied. 8 phenolic compounds were found in C. calyculata shoots, including isoquercitrin, herbacetin, naringenin and naringin – for the first time for this species. 5 compounds were detected in A. polifolia shoots, including isoquercitrin and herbacetin, for the first time for this species. 5 and 4 compounds were identified in L. palustre and E. nigrum shoots, respectively, while quercetin glycosides are predominant in all samples: isoquercitrin, hyperoside and rutin. The fraction of C. calyculata flavonoids at doses of 1, 5, 10 mcg/ml inhibits the production of nitric oxide by macrophages by 30 %, and E. nigrum flavonoids at doses of 100 and 200 mcg/ml, on the contrary, enhance the production of nitrites by macrophages by 33 and 37 %, respectively.Conclusion. A comparative study of the composition of total flavonoid fractions from A. polifolia, C. calyculata, L. palustre, and E. nigrum, which are capable of activating both M1 and M2 polarization of peritoneal macrophages in mice, has been conducted, which requires further in-depth study. The flavonoids C. calyculata and E. nigrum are promising for further study.